Faktor Yang Mempengaruhi Integrasi TIK Dalam Proses Pembelajaran Pada Pondok Pesantren Di Lombok Timur - Mashur Mashur; Taufan Iswandi; Lalu Nurul Yaqin (Universitas Hamzanwadi, 2021)
The trend of information and communication technology (ICT) in education has become something that is very much needed for the development of education and learning in Indonesia. The integration of ICT in the learning process in Islamic boarding schools is still not optimal. Therefore, this study aims to determine the factors that influence ICT integration in the learning process in Islamic boarding schools in the East Lombok. The method used in this study is a qualitative method using several case studies. The data sources on the research were 32 Islamic Boarding School in east Lombok. While the technique of collecting data used survey, interview, and focus group discussion The results of this study revealed two main themes, barriers and support. Barriers are classified into two groups: teacher factors and institutional support factors (Islamic Boarding school). Teachers include lack of time, lack of qualified human resources and the complexity of ICT integration. At the same time, the factors are limited infrastructure, lack of training, lack of access, and lack of technical support. The use of ICT can increase students' creativity. As for the carrying capacity that they believe ICT use during teaching practice can improve their performance, leadership support is also a key factor determining the integration of ICT during the learning process.